AN ANALYSIS OF READING QUESTIONS IN STUDENTS™ WORKSHEET FOR GRADE EIGHT BASED ON BLOOM™S TAXONOMY - Ginting, Rani Crensensia; Hartoyo, Indra; Saragih, Anggraini Thesisia (Universitas Negeri Medan, 2019)
This study aims to : (1) to investigate the application of cognitive levels of bloom taxonomy in reading questions in the worksheet, (2) to investigate the dominant cognitive dimension of Revised Bloom Taxonomy in the worksheet and (3) to write sample reading questions in students™ worksheet. This research was focused on analysing the students™ worksheet which is published by Permata team. The data analysed through data analysis table to categorizing the questions based on theory of Bloom Taxonomy .The finding implies that the number of activities of remembering was the highest percentage in this worksheet, 87.8%.The frequency of remembering is 58 of 66questions. The questions that work on the cognitive level of analyzingrank second with percentage of 6.1%. The third frequency is understanding with 3 question or 4.6 % and the last frequency is creating with 1 question or 1.5 %.The distribution of each category of revised Bloom™s taxonomy within the reading questions is not balanced. Based on the result, the category of remembering that is considered as the lowest level has the highest portion, while the other categories that are categorized as higher level has the low portion. Referring to this findings, the writer tries to develop the reading question in students™ worksheet for grade eight based on Bloom taxonomy to be better by providing some questions that are suitable with low and high order thinking skill.